A dietary analysis of a human skeletal sample from Kichpanha, Belize - Hill, Dustin, author; Magennis, Ann, advisor; Fisher, Christopher, committee member; Kelly, Eugene, committee member (Colorado State University. Libraries, 2011)
The purpose of this study is to improve the understanding of diet at the Maya site of Kichpanha, Belize. Archaeological investigations began at Kichpanha in the late 1980s and continued into the early 1990s. During these investigations much was learned about the history of occupation at Kichpanha and a fairly large skeletal assemblage was recovered. However, preservation of the skeletal material was poor due to the moist conditions and alkalinity of the soil at the site. This made traditional osteological analysis of the recovered remains difficult and limited the types of research that could be carried out on these materials. Previous osteological analyses of these remains concluded that the prevalence of dietary stress or illness among subadults in this population was high as was evident from the high rates of porotic hyperostosis and enamel hypoplasias in the skeletal sample. Frequently these skeletal pathologies among prehistoric populations in the Americas are related to a heavy reliance on maize resulting in iron deficiency anemia. Dental analysis looking at caries rates and calculus also support the hypothesis that the inhabitants of Kichpanha relied heavily on maize. Further analysis of the plant residues found in the dental calculus from individuals from Kichpanha provides direct evidence that maize was part of their diet, but other C3 plants were also included in the diet. The carbon stable isotope data analyzed in this study suggests that maize may not have comprised as large of a proportion of the diet at Kichpanha as the previous osteological data had suggested. Instead the isotope data seems to indicate that the proportion of C3 plants and protein sources in the diet at Kichpanha was relatively high when compared to other Maya sites and that the diet at Kichpanha was fairly stable throughout the site's occupation.
Keywords: Belize; collagen; diet; isotope; Kichpanha; Maya